Pronunciation Errors of the Silent Consonants of Pariskian Junior High School Students - Syafrizal Syafrizal; Sri Wahyuni; Tosi Rut Syamsun (Journal of English Language Teaching and English Linguistics, 2022)
This study aims to determine the general characteristics of pronunciation errors in silent consonant which made by junior high school student and also to determine the interference of Indonesian on the pronunciation of silent consonants in junior high school students. The method that the researcher uses is a qualitative descriptive method, and for the data, the researcher recorded the voices of six junior high school students pronouncing the words that contain silent consonant. There are twenty word which contain silent consonant for every subject. By using error analysis, the researcher diagnoses the errors made by junior high school students into several categories, and by using analysis comparison, he compared the mistakes made by junior high school students with the interference of Indonesian language in pronouncing English words that contain silenct consonant.